2012
DOI: 10.1177/1420326x11433224
|View full text |Cite
|
Sign up to set email alerts
|

Parametric Evaluation of Indoor Particulate Matters in Elementary Schools in the Central Parts of Tehran

Abstract: The objective of this work was to evaluate the indoor-outdoor particle size distribution in elementary schools located in central parts of Tehran and to evaluate those parameters that could be influencing the indoor particles concentrations in the classrooms. Concentrations of particles including PM10, PM2.5 and PM1.0, as some of the main air pollutants in Tehran, were measured in the schools, during winter 2009. It was found that the average indoor concentrations of PM10, PM2.5 and PM1.0 were 274 µg/m3, 42 µg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 27 publications
3
18
0
Order By: Relevance
“…Metabolic activities for building occupants such as respiration, perspiration, running and playing could also contribute to the sources of air pollutants inside the classroom. These results are in agreement with Halek et al (2012) who noted that indoor PM concentrations were higher indoors than outdoor. In selected Dutch schools, indoor concentrations of PM 10 were considerably higher than outdoor ones, especially during school hours, and increases in indoor PM10 were most probably connected with re-suspension of coarse particles (Janssen et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Metabolic activities for building occupants such as respiration, perspiration, running and playing could also contribute to the sources of air pollutants inside the classroom. These results are in agreement with Halek et al (2012) who noted that indoor PM concentrations were higher indoors than outdoor. In selected Dutch schools, indoor concentrations of PM 10 were considerably higher than outdoor ones, especially during school hours, and increases in indoor PM10 were most probably connected with re-suspension of coarse particles (Janssen et al, 1999).…”
Section: Discussionsupporting
confidence: 93%
“…The mean concentrations of indoor PMs were equal to 40 µg/m 3 for PM 2.5 in Baltimore (USA) (McCormack, et al, 2008). Average indoor concentrations of PM 10 , PM 2.5 and PM 1 were 274 µg/m 3 , 42 µg/m 3 and 19 µg/m 3 , respectively, in elementary schools located in central parts of Tehran (Halek et al, 2012). Average PM 10 concentration was 143.3 μg/m 3 in schools located in Kuala Terengganu (Ismail et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…High concentrations of PM 10 could be due to resuspension of chalk dust, skin fl aks, and insect dander that can increase the particle concentration when the students are active. In Tehran, Halek et al (17) reported mean indoor classroom PM 1 , PM 2.5 , and PM 10 of 19 μg m -3 , 42 μg m -3 , and 274 μg m -3 , respectively. Mean PM 2.5 and PM 10 concentrations were lower than in our study (46.6 μg m -3 and 400.9 μg m -3 , respectively), whereas mean indoor PM 1 concentration and mean outdoor PM 2.5 in our study were similar with those reported by in Tehran (17.6 μg m -3 and 36.9 μg m -3 vs. 19 μg m -3 and 38 μg m -3 , respectively).…”
Section: Resultsmentioning
confidence: 97%
“…School children, the elderly, and other groups of people more susceptible to the effects of poor air quality spend even more time indoors (11). Several studies have reported high concentrations of PM in classrooms (12)(13)(14)(15)(16)(17). Major studies about personal exposure to particles (18,19) have found poor correlation between personal exposure to fi ne particulate matter and outdoor air particle concentrations, but they have also reported good correlation between personal exposure and indoor air particle concentrations.…”
mentioning
confidence: 92%
“…The city is surrounded by mountains with an altitude of about 3800–1000 m in North-South and East which exacerbates pollution in the city [ [4] , [5] , [6] , [7] ]. Additional factors such as fast urbanization, uncontrolled emissions from cars and lack of infrastructures have caused a drop in the air quality in Tehran [ 8 ]. Vehicles considered the main cause of air pollution in Tehran.…”
Section: Introductionmentioning
confidence: 99%